Evaluation of apoptotic effects of mPEG-b-PLGA coated iron oxide nanoparticles as a eupatorin carrier on DU-145 and LNCaP human prostate cancer cell lines - Marziyeh Shalchi Tousi; Houri Sepehri; Sepideh Khoee; Mahdi Moridi Farimani; Ladan Delphi; Fariba Mansourizadeh (Elsevier, 2021)
Many studies have so far confirmed the efficiency of phytochemicals in the treatment of prostate cancer. Eupatorin, a flavonoid with a wide range of phytomedical activities, suppresses proliferation of and induces apoptosis of multiple cancer cell lines. However, low solubility, poor bioavailability, and rapid degradation limit its efficacy. The aim of our study was to evaluate whether the use of mPEG-b-poly (lactic-co-glycolic) acid (PLGA) coated iron oxide nanoparticles as a carrier could enhance the therapeutic efficacy of eupatorin in DU-145 and LNcaP human prostate cancer cell lines. Nanoparticles were prepared by the co-precipitation method and were fully characterized for morphology, surface charge, particle size, drug loading, encapsulation efficiency and in vitro drug-release profile. The inhibitory effect of nanoparticles on cell viability was evaluated by MTT test. Apoptosis was then determined by Hoechest staining, cell cycle analysis, NO production, annexin/propidium iodide (PI) assay, and Western blotting. The results indicated that eupatorin was successfully entrapped in Fe3O4@mPEG-b-PLGA nanoparticles with an efficacy of (90.99 ± 2.1)%. The nanoparticle's size was around (58.5 ± 4) nm with a negative surface charge [(−34.16 ± 1.3) mV]. In vitro release investigation showed a 30% initial burst release of eupatorin in 24 h, followed by sustained release over 200 h. The MTT assay indicated that eupatorin-loaded Fe3O4@mPEG-b-PLGA nanoparticles exhibited a significant decrease in the growth rate of DU-145 and LNcaP cells and their IC50 concentrations were 100 μM and 75 μM, respectively. Next, apoptosis was confirmed by nuclear condensation, enhancement of cell population in the sub-G1 phase and increased NO level. Annexin/PI analysis demonstrated that eupatorin-loaded Fe3O4@mPEG-b-PLGA nanoparticles could increase apoptosis and decrease necrosis frequency. Finally, Western blotting analysis confirmed these results and showed that Bax/Bcl-2 ratio and the cleaved caspase-3 level were up-regulated by the designing nanoparticles. Encapsulation of eupatorin in Fe3O4@mPEG-b-PLGA nanoparticles increased its anticancer effects in prostate cancer cell lines as compared to free eupatorin. Based on these results, this formulation can provide a sustained eupatorin-delivery system for cancer treatment with the drug remaining active at a significantly lower dose, making it a suitable candidate for pharmacological uses.